Factors affecting sputum and culture conversion in pulmonary tuberculosis patients on directly observed treatment, short-course - Boorsu, Suresh Kumar; Myreddy, Venkata Subba Narasimha; Kandati, Jithendra; Ponugoti, Muni Lakshmi (International Journal of Research in Medical Sciences, 2016)
Background: Sputum smear positive patients are infectious for a variable period after starting of treatment. Patients receiving anti-tuberculosis treatment by DOTS become noninfectious and times taken to become non-infectious are assessed by sputum smear conversion (SSC) by smear microscopy and culture conversion by growth on Lowenstein-Jensen medium. The aim of present study was to determine the time taken for SSC and culture conversion and factors delaying it. Methods: A prospective cross-sectional study was undertaken in a tertiary hospital over a period of one year from January 2015 to December 2015 by Department of Respiratory medicine. 150 patients diagnosed as pulmonary tuberculosis by sputum smear microscopy and on DOTS were included and followed at regular intervals of 4th, 8th, 12th, 16th and 20th week or until they were sputum and culture negative which was earlier. At each follow-up sputum, smear and culture were done as per standard guidelines. Results: 150 patients were enrolled which included 63 (42%) males and 87 (58%) females with mean age of 36.41 years and all were followed up. Fever was the most common clinical symptom (98.67%). 146 patients (97.33%) underwent sputum and culture conversion. The median time taken for sputum conversion for cases in the study was by the end of 4th week [day 28] and culture conversion was by end of 5th week [day 35]. 4 cases were positive for sputum and culture which were seropositive for HIV. Conclusions: Smear-positive patients are infectious to close contacts and to the community. Hence initiation of infection control measures should be applied until the patient is non-infectious. The results of our study reveal that patients of smear positive pulmonary tuberculosis continue to expel the bacilli for a considerable period of time after initiation of DOTS regimen. There is a strong need to reinforce infection control measures until the patients are judged noninfectious.